A new fiber surface impregnation treatment system and impregnation method

CN122942335APending Publication Date: 2026-10-20BEIJING UNIV OF CHEM TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510463048.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]为了解决现有RFL浸渍体系对人体毒害较大的技术问题,本发明提供了一种新型纤维表面浸渍处理体系及浸渍方法

Benefits of technology

[0070]本发明提出了一种基于生物基苯并噁嗪树脂的新型纤维表面浸渍处理体系,根据不同纤维种类、用途可以选择采用单浴浸渍处理或双浴浸渍处理,处理后的纤维具有优异的粘合效果,可以达到替代传统RFL体系的目的。具体来说,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005357712030000031
    Figure BDA0005357712030000031
  • Figure BDA0005357712030000041
    Figure BDA0005357712030000041
  • Figure BDA0005357712030000101
    Figure BDA0005357712030000101
Patent Text Reader

Abstract

This invention relates to the field of fiber impregnation technology, specifically to a novel fiber surface impregnation system and method. The invention utilizes specific bio-based aldehydes, bio-based amines, and bio-based polyphenols to polymerize a novel bio-based benzoxazine resin. This novel bio-based benzoxazine resin is then used as the main component of the impregnation system, combined with rubber latex, to form a novel fiber surface treatment impregnation system. The fiber surface treatment impregnation system provided by this invention uses only biological materials, achieving bio-based and environmentally friendly impregnation; moreover, it achieves good curing effects in the impregnation system without the need for isocyanates and additives, thereby achieving excellent interfacial adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber impregnation technology, and more specifically, to a novel fiber surface impregnation treatment system and impregnation method. Background Technology

[0002] Fiber / rubber composites are widely used in passenger car tires, heavy-duty truck tires, aircraft tires, high-load conveyor belts, and special pressure-resistant hoses. The high-performance fibers in the composite material provide strong rigidity to bear the stress, while the rubber matrix provides significant elasticity to cope with the large strain generated by deformation. The significant difference in polarity and modulus between fibers and rubber means that the stress transfer at their interface determines the overall performance of the composite material. However, the substantial difference in polarity and modulus between fibers and rubber results in relatively weak interfacial interaction.

[0003] Currently, fiber impregnation is a common method to enhance the adhesion between fibers and rubber. The most mature solution involves impregnating the fiber material with resorcinol-formaldehyde-latex (RFL), which can significantly improve the bond strength. However, the resorcinol and formaldehyde used in this method are highly toxic to humans and have been classified as carcinogens by the International Agency for Research on Cancer (IARC). Consequently, many countries worldwide have enacted laws and regulations prohibiting the use of resorcinol and formaldehyde in tire production. Therefore, there is an urgent need to develop new, environmentally friendly fiber impregnation systems to replace the traditional toxic RFL impregnation system.

[0004] Patents US20150314644A1, US2012041113A1, and US5565507A disclose environmentally friendly impregnation solutions based on epoxy resins. Specifically, US2015314644A1 discloses an adhesive formulation consisting of rubber latex, an epoxy compound, and a polyamine with a molecular weight greater than 190 Daltons. This composition produces an adhesion level between the fiber skeleton material and the rubber compound that is close to that of conventional RFL systems. US2012041113A1 discloses an impregnation solution composed of epoxy resin, an amino curing agent, end-capped isocyanate, and rubber latex, which can be used to treat nylon and polyester fibers. US5565507A discloses an impregnation solution composed of a trifunctional or higher epoxy resin and a latex containing carboxyl, amino, or pyridine groups, which can be used to enhance the adhesion between woven fabrics and rubber.

[0005] Patents WO2021000918A1, US2005147817A1, and US2005255773A1 disclose environmentally friendly impregnation solutions based on maleic anhydride-modified polymers. WO2021000918A1 discloses an impregnation system composed of maleic anhydride-modified polymers, epoxy resin, blocked isocyanate, curing agent, rubber latex, and reinforcing fillers, achieving RFL-level treatment effects. US2005147817A1 discloses an impregnation solution composed of semi-esterified maleic anhydride-modified polybutadiene, carbon black, and latex, which can effectively improve the adhesion between fibers and EPDM rubber. US2005255773A1 discloses an environmentally friendly impregnation solution composed of maleic anhydride-modified polyolefin, maleimide resin, vinyl unsaturated carboxylic acid metal salt, and latex, which can significantly improve the adhesion between fibers and rubber.

[0006] Patents US2015315410A1 and US20150259560A1 disclose environmentally friendly impregnation solutions based on acrylic resin. US2015315410A1 discloses an impregnation solution composed of carboxyl-containing acrylic resin, epoxy resin, blocked isocyanate, and latex, which exhibits slightly better adhesion than RFL. US20150259560A1 discloses an impregnation solution composed of acrylic resin, epoxy compound, isocyanate, and rubber latex, used to improve the adhesion between fibers and between fabrics and rubber.

[0007] The aforementioned non-RFL environmentally friendly impregnation systems avoid the use of toxic substances such as resorcinol and formaldehyde; however, all of the aforementioned non-RFL impregnation systems are developed using petroleum-based compounds as raw materials, which are expensive; and due to various reasons, such as high raw material costs, complex configuration processes, and stringent process requirements, the aforementioned non-RFL environmentally friendly impregnation treatment technologies have not been commercialized. Summary of the Invention

[0008] To address the technical problem that existing RFL impregnation systems are highly toxic to humans, this invention provides a novel fiber surface impregnation treatment system and impregnation method.

[0009] This invention first uses specific bio-based aldehydes, bio-based amines, and bio-based polyphenols to polymerize a novel bio-based benzoxazine resin. Then, the novel bio-based benzoxazine resin is used as the main component of the impregnation system and combined with rubber latex to form a novel fiber surface treatment impregnation system.

[0010] The fiber surface treatment impregnation system provided by this invention uses only biological materials as raw materials, thus realizing the bio-based and environmentally friendly nature of the impregnation system; moreover, it can play a good curing role in the impregnation system without the addition of isocyanate and additives, thereby achieving a good interfacial adhesion effect.

[0011] One of the objectives of this invention is to provide a novel fiber surface treatment impregnation system.

[0012] The impregnation system comprises the following components;

[0013] Each component is expressed in parts by weight:

[0014]

[0015] 10-30 parts by weight of bio-based benzoxazine resin solution, preferably 15-25 parts by weight; for example, 20 parts by weight.

[0016] Solvent A is an aqueous solvent, preferably water, and more preferably deionized water.

[0017] The rubber latex can be any one or more existing rubber latexes suitable for fiber surface treatment impregnation systems. Preferably, the rubber latex is selected from one or more of butyl pyridine latex, styrene-butadiene latex, styrene-butadiene pyridine latex, chloroprene latex, nitrile latex, chlorosulfonated polyethylene latex, and natural latex; for example, the rubber latex is styrene-butadiene-vinylpyridine latex. The styrene-butadiene latex is preferably carboxylated styrene-butadiene latex; the nitrile latex is preferably carboxylated nitrile latex; and the natural latex is preferably epoxidized natural latex.

[0018] The solid content of the rubber latex can be conventional. Preferably, the solid content of the rubber latex is 20-60 wt%, for example, 40 wt%.

[0019] As a specific embodiment, the rubber latex is a styrene-butadiene-vinylpyridine latex with a solid content of 40 wt%.

[0020] The filler is an optional component. Compared to an impregnation system without filler, an impregnation system containing filler has better adhesive properties. Therefore, as a preferred embodiment, the bio-based environmentally friendly impregnation system for the fiber surface contains filler; based on 100 parts by weight of solvent A, the amount of filler is 0.05-2 parts by weight, preferably 0.05 parts by weight.

[0021] The filler can be any one or more existing fillers suitable for fiber surface treatment impregnation systems. As a preferred embodiment, the filler is selected from one or more of the following: nano-silica, carbon black, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, nano-calcium oxide, nano-calcium carbonate, carbon nanotubes, attapulgite, nano-cellulose, silicide, nano-aramid fiber, basalt fiber, nano whiskers, graphene oxide, montmorillonite, mica, kaolin, and hydrotalcite. Preferably, it is selected from one or more of the following: nano-cellulose, nano-silica, montmorillonite, and carbon nanotubes.

[0022] The filler is preferably a filler treated with a surface modifier. The surface modifier is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, alkylsilane coupling agents, isocyanate-based silane coupling agents, and polyether silane coupling agents, preferably from one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidoxypropyltrimethoxysilane (KH560), γ-methacryloyloxypropyltrimethoxysilane (KH570), γ-mercaptopropyltriethoxysilane (KH580), bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si69), and vinyltriethoxysilane (A151).

[0023] The bio-based benzoxazine resin in the described bio-based benzoxazine resin solution differs in structure and properties from existing benzoxazine resins and is self-made according to this invention. The bio-based benzoxazine resin is synthesized by the polymerization reaction of bio-based aldehydes, bio-based polyamines, and bio-based polyphenols. Testing revealed that the bio-based benzoxazine resin contains repeating structural units as shown in Formula I:

[0024]

[0025] The structural formula of the bio-based benzoxazine resin is: The positions of R, R′, and R″ are reaction sites, and R, R′, and R″ represent repeating structural units as shown in Formula I; they can extend outward from the positions of R, R′, and R″ to form molecular chains and polymer networks.

[0026] The bio-based benzoxazine resin has a number average molecular weight of 500-3000. It exhibits good water solubility, can be used in impregnation systems, and can undergo further curing reactions.

[0027] Compared with existing benzoxazine resins, the bio-based benzoxazine resin provided by this invention retains a large number of active groups such as hydroxyl and amino groups, which can form hydrogen bonds with the fiber surface, thus improving the interfacial adhesion effect.

[0028] The bio-based benzoxazine resin solution is prepared from raw materials comprising the following components;

[0029] Each component is expressed in parts by weight:

[0030] Solvent B, 20 parts by weight;

[0031] 3-8 parts by weight of bio-based aldehyde, preferably 4-7 parts by weight; for example, 4.2 parts by weight, 6.3 parts by weight.

[0032] 1-5 parts by weight of bio-based polyamine, preferably 3-5 parts by weight; for example, 3.3 parts by weight or 4.6 parts by weight; 0.1-5 parts by weight of bio-based polyphenol, preferably 3-5 parts by weight; for example, 3.0 parts by weight or 4.2 parts by weight.

[0033] Solvent B is an aqueous solvent, preferably water, and more preferably deionized water.

[0034] The bio-based aldehyde is selected from one or more of salicylaldehyde, 5-hydroxymethylfurfural, vanillin, eugenol, cinnamaldehyde, benzaldehyde, phenylacetaldehyde, and cinnamaldehyde, preferably one or more of salicylaldehyde, 5-hydroxymethylfurfural, and vanillin.

[0035] The bio-based polyamine is selected from one or more of L-lysine, furfurylamine, chitosan, and natural melanin, preferably one or more of L-lysine and furfurylamine.

[0036] The bio-based polyphenols are selected from one or more of catechins, tea polyphenols, tannic acid, guaiacol, lignin, apigenin, resveratrol, naringenin, gallic acid, catechins, and apple polyphenols, preferably one or more of catechins, tea polyphenols, tannic acid, and lignin.

[0037] The bio-based aldehyde, bio-based polyamine, and bio-based polyphenol are polymerized in solvent B at 30-50°C to obtain a bio-based benzoxazine resin solution. Specifically, any one or more of the bio-based aldehydes, bio-based polyamines, and bio-based polyphenols can be selected to prepare the bio-based benzoxazine resin solution. For example, salicylaldehyde, L-lysine, and catechin can be selected to prepare the bio-based benzoxazine resin solution; vanillin, L-lysine, and tannic acid can also be selected to prepare the bio-based benzoxazine resin solution. Compared to the bio-based benzoxazine resin solution prepared by vanillin, L-lysine, and tannic acid, the bio-based benzoxazine resin solution prepared by salicylaldehyde, L-lysine, and catechin exhibits better H-extraction force, higher peel force, and longer fatigue life when used in the impregnation system of this invention, resulting in better adhesion. Therefore, as a preferred embodiment, the bio-based benzoxazine resin solution is prepared from raw materials containing salicylaldehyde, L-lysine, and catechin.

[0038] When a bio-based benzoxazine resin solution prepared by reacting salicylaldehyde, L-lysine, and catechin is selected, the amount of salicylaldehyde used is 4-7 parts by weight, the amount of L-lysine used is 3-5 parts by weight, and the amount of catechin used is 3-5 parts by weight, based on 20 parts by weight of solvent B.

[0039] Therefore, as a preferred embodiment, the bio-based benzoxazine resin solution is prepared from raw materials comprising the following components;

[0040] Each component is expressed in parts by weight:

[0041] Solvent B, 20 parts by weight;

[0042] Salicylaldehyde 4-7 parts by weight;

[0043] 3-5 parts by weight of L-lysine;

[0044] Catechins 3-5 parts by weight.

[0045] The preparation method of the bio-based benzoxazine resin solution includes: adding a bio-based aldehyde to solvent B and stirring to dissolve it at 30-50°C; adding a bio-based polyamine and stirring for 1-3 hours; and adding a bio-based polyphenol and stirring for 3-8 hours to obtain the bio-based benzoxazine resin solution. The bio-based benzoxazine resin solution requires no post-treatment and can be directly used as a component of the impregnation system.

[0046] The bio-based benzoxazine resin solution comprises bio-based benzoxazine resin and solvent B. The content of bio-based benzoxazine resin in the bio-based benzoxazine resin solution is 15-50 wt%, preferably 25-45 wt%.

[0047] One of the objectives of this invention is to provide an impregnation system that can be used for treating various fibers. Specifically, the fibers can be one or more of the following: rayon, nylon 6, nylon 66, meta- or para-aramid fibers, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide, and carbon fiber. The fibers can be selected from one or more of the following forms: monofilament, towed yarn, twisted yarn, canvas, and tire cord fabric.

[0048] When impregnating fibers using the impregnation system described in one of the invention's objectives, conventional impregnation methods can be employed. Depending on the fiber type and intended use, single-bath or double-bath impregnation treatments can be selected. For example, double-bath treatment is suitable for heavy-denier nylon cords, aramid cords, polyester cords, and aramid / nylon blended cords.

[0049] The second objective of this invention is to provide a method for impregnating the surface of fibers.

[0050] The impregnation method includes:

[0051] Step 1): Place the fiber in the impregnation system as described in one of the invention's objectives, and impregnate at 15-40°C for 2-60 seconds.

[0052] Step 2): After impregnation, remove the fiber and dry it at 100-150℃ for 1-10 minutes, then cure it at 180-260℃ for 1-10 minutes.

[0053] As a preferred embodiment: Before step 1), the pH of the impregnation system is adjusted to alkaline using an alkaline solution, preferably between 8.0 and 11.0. The alkaline solution may be ammonia.

[0054] As a preferred method: Before step 1), immerse the fiber in the impregnation solution at 15-40℃ for 2-30 seconds, then remove it and dry it at 100-150℃ for 1-10 minutes, and then cure it at 180-260℃ for 1-10 minutes. This is a double-bath treatment.

[0055] The impregnation solution can be a conventional impregnation solution. As a preferred embodiment, the impregnation solution comprises, by weight: 100 parts solvent; 0.5 to 4 parts epoxy resin, preferably 0.5 to 2.5 parts epoxy resin; and 2 to 10 parts blocked isocyanate, preferably 4 to 8 parts isocyanate.

[0056] The blocked isocyanate is a blocked isocyanate formed from an isocyanate and a capping agent. The blocked isocyanate can be any existing blocked isocyanate used in the art. Preferably, the isocyanate is selected from one or more of trimethyl-1,6-hexamethylene diisocyanate, tetramethylene diisocyanate, tetramethyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenyl diisocyanate, 1,4-phenyl diisocyanate, isophorone diisocyanate, and diphenylmethane diisocyanate, more preferably diphenylmethane diisocyanate.

[0057] The epoxy resin can be a mono- or multi-component epoxy resin that is soluble in solvent A or rubber latex. Preferably, the epoxy resin is selected from one or more of the following: bisphenol A type epoxy resin, epoxidized linear phenolic resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,2-propanediol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane diglycidyl ether, tetraphenol ethane tetraglycidyl ether epoxy resin, sorbitol diglycidyl ether, resorcinol diglycidyl ether type epoxy resin, and bisresorcinol formaldehyde tetraglycidyl ether; more preferably, it is selected from one or more of the following: glycerol diglycidyl ether, ethylene glycol diglycidyl ether, and sorbitol diglycidyl ether, which have good water solubility. As one embodiment, the epoxy resin is composed of a first epoxy resin and a second epoxy resin in any proportion, wherein the first epoxy resin is sorbitol glycidyl ether and the second epoxy resin is ethylene glycol diglycidyl ether and / or glycerol glycidyl ether.

[0058] An impregnation method for a fiber surface, one specific embodiment of which includes the following steps:

[0059] Step A): Impregnate the fibers in the impregnation solution;

[0060] Step B): Dry the fibers treated in step A), and then cure them;

[0061] Step C): Adjust the pH of the impregnation system described in one of the objectives of the invention to 8.0-11.0 using ammonia; place the fibers treated in step B) into the impregnation system for impregnation;

[0062] Step D): Dry and cure the fibers treated in step C);

[0063] In step A), the immersion temperature is 15-40℃ and the time is 2-30s;

[0064] In step B), the drying temperature is 100-150℃ and the time is 1-10 min;

[0065] In step B), the curing temperature is 180-260℃ and the time is 1-10 min;

[0066] In step C), the immersion temperature is 15-40℃ and the time is 2-60s;

[0067] In step D), the drying temperature is 100-150℃ and the time is 1-10 min;

[0068] In step D), the curing temperature is 180-260℃ and the time is 1-10 min.

[0069] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0070] This invention proposes a novel fiber surface impregnation system based on bio-based benzoxazine resin. Depending on the fiber type and application, single-bath or double-bath impregnation treatment can be selected. The treated fibers exhibit excellent adhesion, achieving the goal of replacing the traditional RFL system. Specifically,

[0071] 1. The novel fiber surface impregnation treatment system provided by this invention uses bio-based raw materials, which are free of harmful components such as resorcinol and formaldehyde. It is green and environmentally friendly, harmless to humans and the environment, and has renewable characteristics. Furthermore, the novel fiber surface impregnation treatment system provided by this invention is suitable for treating various fibers. The treated fibers exhibit excellent adhesion, significantly improve fatigue resistance, and do not cause significant damage to fiber strength or affect their use.

[0072] 2. The novel fiber surface impregnation treatment system provided by the present invention further regulates the modulus of the impregnation layer by adding nanofillers, and constructs a modulus transition layer between the fiber and the rubber, which can improve the interfacial adhesion.

[0073] 3. The bio-based benzoxazine resin solution prepared by this invention is stable and its viscosity does not change much when stored at room temperature, which is beneficial for the long-term storage and transportation of the impregnation solution.

[0074] 4. The preparation process of the impregnation system and the fiber surface treatment process in this invention are simple and conducive to industrial production. Attached Figure Description

[0075] Figure 1 The Fourier transform infrared spectrum of the bio-based benzoxazine resin prepared in Example 1 is shown. Detailed Implementation

[0076] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0077] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available. Among them:

[0078] Salicylaldehyde, CAS 90-02-8, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0079] L-Lysine, CAS 56-87-1, purchased from Shanghai Dibai Biotechnology Co., Ltd.

[0080] Catechins, CAS 7295-85-4, purchased from Shanghai Dibai Biotechnology Co., Ltd.;

[0081] Vanillin, CAS121-33-5, purchased from Shanghai Myriel Biochemical Technology Co., Ltd.

[0082] Tannic acid, CAS1401-55-4, purchased from Shanghai Mairui Biochemical Technology Co., Ltd.

[0083] Styrene-butadiene-vinylpyridine latex (VP latex), grade VP-15, purchased from Jiangsu Yatai Chemical Co., Ltd.

[0084] Sorbitol glycidyl ether, CAS 68412-01-1, purchased from Nan Ya Epoxy Resin Co., Ltd.

[0085] ε-caprolactam-terminated diphenylmethane diisocyanate, brand name CBI 50, was purchased from Changzhou Keying Chemical Co., Ltd.

[0086] Carbon nanotubes, CAS1333-86-4, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0087] Resorcinol, CAS108-46-3, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0088] Formaldehyde, CAS 50-00-0, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0089] Example 1

[0090] Preparation of bio-based benzoxazine resin solution:

[0091] Prepare the ingredients:

[0092]

[0093] Salicylic aldehyde was added to deionized water, and the solution was stirred at 35°C and 500 rpm for 0.5 h. L-lysine was added and stirred for 3 h, followed by the addition of catechin and stirring for 4.5 h to obtain a bio-based benzoxazine resin solution.

[0094] The prepared bio-based benzoxazine resin solution was dried (to remove deionized water) to obtain the bio-based benzoxazine resin.

[0095] The Fourier transform infrared spectrum of the prepared bio-based benzoxazine resin is shown below. Figure 1 As shown. From Figure 1 The presence of methyl and methylene stretching vibration peaks (2900), ether stretching vibration peak at CO (1230), and characteristic peak of the oxazine ring (950) indicates the presence of a benzoxazine structure in the bio-based benzoxazine resin; it contains repeating structural units as shown in Formula I:

[0096] The number-average molecular weight of the prepared bio-based benzoxazine resin was 2556.

[0097] A novel fiber surface impregnation treatment system based on bio-based benzoxazine resin, with the following formulation by weight:

[0098] 100 parts by weight of deionized water;

[0099] 20 parts by weight of bio-based benzoxazine resin solution;

[0100] Sodium hydroxide 0.3 parts by weight;

[0101] 65 parts by weight of styrene-butadiene-vinylpyridine latex (40 wt% solids content).

[0102] Preparation method of impregnation treatment system:

[0103] A bio-based benzoxazine resin solution and sodium hydroxide were dissolved in deionized water at a predetermined weight ratio and stirred at 25°C and 500 rpm for 1.5 h to obtain a mixed solution. Subsequently, the mixed solution was added to styrene-butadiene-vinylpyridine latex and stirred at 25°C and 500 rpm for 2 h to obtain an impregnation treatment system; during the stirring process, the pH was adjusted to 10 by adding ammonia.

[0104] Impregnation treatment method:

[0105] Nylon 66 (1400 dtex / 2) cord was immersed in the impregnation solution for 3 seconds, then dried and cured in an oven to obtain the impregnated cord. The drying temperature was 140℃ and the drying time was 40s. The curing temperature was 210℃ and the curing time was 40s.

[0106] Example 2

[0107] Preparation of bio-based benzoxazine resin solution:

[0108] Prepare the ingredients:

[0109]

[0110] The preparation method of the bio-based benzoxazine resin solution is the same as in Example 1. The number-average molecular weight of the prepared bio-based benzoxazine resin is 862.

[0111] A novel fiber surface impregnation treatment system based on bio-based benzoxazine resin, with the following formulation by weight:

[0112] 100 parts by weight of deionized water;

[0113] 20 parts by weight of bio-based benzoxazine resin solution;

[0114] Sodium hydroxide 0.3 parts by weight;

[0115] 65 parts by weight of styrene-butadiene-vinylpyridine latex (40 wt% solids content).

[0116] The preparation method of the impregnation treatment system is the same as in Example 1.

[0117] The impregnation treatment method is the same as in Example 1. The treated fiber cord is nylon 66 (1400 dtex / 2).

[0118] Example 3

[0119] A novel fiber surface impregnation treatment system based on bio-based benzoxazine resin, with the following formulation by weight:

[0120] 100 parts by weight of deionized water;

[0121] 20 parts by weight of the bio-based benzoxazine resin solution prepared in Example 1;

[0122] Sodium hydroxide 0.3 parts by weight;

[0123] 0.05 parts by weight of carbon nanotubes;

[0124] 65 parts by weight of styrene-butadiene-vinylpyridine latex (40 wt% solid content);

[0125] Preparation method of impregnation treatment system:

[0126] Carbon nanotubes and 15 parts by weight of deionized water were added to a beaker and stirred at 25°C and 800 rpm for 1 hour. Then, ultrasonic stirring was performed. The ultrasonic equipment had a power of 400 W and the ultrasonic stirring time was 1 hour to obtain a carbon nanotube dispersion.

[0127] A bio-based benzoxazine resin solution, sodium hydroxide, and carbon nanotube dispersion were added to the remaining deionized water at a predetermined weight ratio, and stirred at 25°C and 500 rpm for 1.5 h to obtain a mixed solution. Subsequently, the mixed solution was added to styrene-butadiene-vinylpyridine latex, and stirred at 25°C and 500 rpm for 2 h to obtain an impregnation treatment system; during the stirring process, the pH was adjusted to 10 by adding ammonia.

[0128] The impregnation treatment method is the same as in Example 1. The treated fiber cord is nylon 66 (1400 dtex / 2).

[0129] Example 4

[0130] A novel fiber surface impregnation treatment system based on bio-based benzoxazine resin, with the following formulation by weight:

[0131] 100 parts by weight of deionized water;

[0132] 20 parts by weight of the bio-based benzoxazine resin solution prepared in Example 1;

[0133] Sodium hydroxide 0.3 parts by weight;

[0134] 0.05 parts by weight of modified carbon nanotubes;

[0135] 65 parts by weight of styrene-butadiene-vinylpyridine latex (40 wt% solids content).

[0136] 0.05 parts by weight of modified carbon nanotubes means that the carbon nanotubes in the modified carbon nanotubes are 0.05 parts by weight.

[0137] Preparation method of impregnation treatment system:

[0138] Carbon nanotubes were mixed with 15 parts by weight of deionized water to obtain a carbon nanotube dispersion. A mixed solution of modifier KH550 / ethanol (KH550 / ethanol volume ratio 2:1, ethanol (purity ≥95wt%)) (KH550 amount is 10wt% of carbon nanotube amount) was slowly added to the carbon nanotube dispersion, and the mixture was stirred at 25℃ and 300rpm for 1h, followed by ultrasonic stirring. The ultrasonic equipment power was 400W, and the ultrasonic stirring time was 1h to obtain a modified carbon nanotube dispersion.

[0139] The bio-based benzoxazine resin solution and sodium hydroxide were added to the remaining deionized water at a predetermined weight ratio, and stirred at 25°C and 500 rpm for 6 hours. After adding styrene-butadiene-vinylpyridine latex, the mixture was stirred at 25°C and 500 rpm for 2 hours to obtain a mixed solution. During the stirring process, the pH was adjusted to 10 by adding ammonia.

[0140] The modified carbon nanotube dispersion was mixed with the mixed solution and stirred at 25°C and 500 rpm for 1.5 h to obtain the impregnation treatment system.

[0141] The impregnation treatment method is the same as in Example 1. The treated fiber cord is nylon 66 (1400 dtex / 2).

[0142] Example 5

[0143] A novel fiber surface impregnation treatment system based on bio-based benzoxazine resin, with the following formulation by weight:

[0144] 100 parts by weight of deionized water;

[0145] 20 parts by weight of the bio-based benzoxazine resin solution prepared in Example 1;

[0146] Sodium hydroxide 0.3 parts by weight;

[0147] 0.05 parts by weight of modified carbon nanotubes;

[0148] 65 parts by weight of styrene-butadiene-vinylpyridine latex (40 wt% solids content).

[0149] 0.05 parts by weight of modified carbon nanotubes means that the carbon nanotubes in the modified carbon nanotubes are 0.05 parts by weight.

[0150] The preparation method of the impregnation treatment system is the same as in Example 4.

[0151] Impregnation treatment method:

[0152] Nylon 66 (1400 dtex / 2) cord was immersed in the impregnation solution for 3 seconds, then dried and cured in an oven to obtain the impregnated cord. The drying temperature was 150℃ and the drying time was 70s. The curing temperature was 230℃ and the curing time was 70s.

[0153] Example 6

[0154] First bath impregnation solution components:

[0155] 1.5 parts by weight of sorbitol glycidyl ether;

[0156] 3.7 parts by weight of ε-lactam-terminated diphenylmethane diisocyanate;

[0157] 100 parts by weight of deionized water.

[0158] Preparation method of the first bath impregnation solution: Sorbitol glycidyl ether, ε-caprolactam-terminated diphenylmethane diisocyanate and deionized water are added to a beaker in proportion and stirred at 500 rpm for 1 h at 25 °C.

[0159] Second bath impregnation solution components:

[0160] 100 parts by weight of deionized water;

[0161] 20 parts by weight of the bio-based benzoxazine resin solution prepared in Example 1;

[0162] Sodium hydroxide 0.3 parts by weight;

[0163] 65 parts by weight of styrene-butadiene-vinylpyridine latex.

[0164] Preparation method of the second bath impregnation solution:

[0165] A bio-based benzoxazine resin solution and sodium hydroxide were dissolved in deionized water at a predetermined weight ratio and stirred at 25°C and 500 rpm for 1.5 h to obtain a mixed solution. Subsequently, the mixed solution was added to styrene-butadiene-vinylpyridine latex and stirred at 25°C and 500 rpm for 2 h to obtain an impregnation treatment system; during the stirring process, the pH was adjusted to 10 by adding ammonia.

[0166] Impregnation treatment method:

[0167] First, the high-denier nylon 66 (2100 dtex / 3) cord was placed in the first impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 72 seconds, and cured at 230°C for 70 seconds. Then, the fibers were placed in the second impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 70 seconds, and cured at 230°C for 70 seconds to obtain the impregnated cord.

[0168] Example 7

[0169] The composition and preparation method of the first bath impregnation solution are the same as in Example 6.

[0170] Preparation of bio-based benzoxazine resin solution:

[0171] raw material:

[0172]

[0173] The preparation method of the bio-based benzoxazine resin solution is the same as in Example 1. The number-average molecular weight of the prepared bio-based benzoxazine resin is 2660.

[0174] Second bath impregnation solution components:

[0175] 100 parts by weight of deionized water;

[0176] 20 parts by weight of bio-based benzoxazine resin solution;

[0177] Sodium hydroxide 0.3 parts by weight;

[0178] 65 parts by weight of styrene-butadiene-vinylpyridine latex.

[0179] The preparation method of the second bath impregnation solution is the same as in Example 6.

[0180] The impregnation treatment method is the same as in Example 6. The treated fiber cord is high-denier nylon 66 (2100 dtex / 3).

[0181] Example 8

[0182] The composition and preparation method of the first bath impregnation solution are the same as in Example 6.

[0183] Second bath impregnation solution components:

[0184] 100 parts by weight of deionized water;

[0185] 20 parts by weight of the bio-based benzoxazine resin solution prepared in Example 7

[0186] Sodium hydroxide 0.3 parts by weight;

[0187] 0.05 parts by weight of modified carbon nanotubes;

[0188] 65 parts by weight of styrene-butadiene-vinylpyridine latex.

[0189] 0.05 parts by weight of modified carbon nanotubes means that the carbon nanotubes in the modified carbon nanotubes are 0.05 parts by weight.

[0190] Preparation method of the second bath impregnation solution:

[0191] Carbon nanotubes were mixed with 15 parts by weight of deionized water to obtain a carbon nanotube dispersion. A mixed solution of modifier KH550 / ethanol (KH550 / ethanol volume ratio 2:1, ethanol (purity ≥95wt%)) (KH550 amount is 10wt% of carbon nanotube amount) was slowly added to the carbon nanotube dispersion, and the mixture was stirred at 25℃ and 300rpm for 1h, followed by ultrasonic stirring. The ultrasonic equipment power was 400W, and the ultrasonic stirring time was 1h to obtain a modified carbon nanotube dispersion.

[0192] The bio-based benzoxazine resin solution and sodium hydroxide were added to the remaining deionized water at a predetermined weight ratio, and stirred at 25°C and 500 rpm for 6 hours. After adding styrene-butadiene-vinylpyridine latex, the mixture was stirred at 25°C and 500 rpm for 2 hours to obtain a mixed solution. During the stirring process, the pH was adjusted to 10 by adding ammonia.

[0193] The modified carbon nanotube dispersion was mixed with the mixed solution and stirred at 25°C and 500 rpm for 1.5 h to obtain the impregnation treatment system.

[0194] The impregnation treatment method is the same as in Example 6. The treated fiber cord is high-denier nylon 66 (2100 dtex / 3).

[0195] Example 9

[0196] The aramid cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Example 7. The impregnation treatment method was the same as in Example 7.

[0197] Example 10

[0198] The aramid cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Example 8. The impregnation treatment method was the same as in Example 8.

[0199] Example 11

[0200] The polyester cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Example 7.

[0201] Impregnation treatment method: First, place the polyester (1670 dtex / 2) cord in the first impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds. Then, place the fiber in the second impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds to obtain the impregnated cord.

[0202] Example 12

[0203] The polyester cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Example 8. The impregnation treatment method was the same as in Example 11.

[0204] Example 13

[0205] The aramid-nylon hybrid cord (AF1670dtex / 2+PA1400dtex / 1) was treated with the first and second impregnation solutions prepared in Example 7. The impregnation treatment method was the same as in Example 7.

[0206] Example 14

[0207] The aramid-nylon hybrid cord (AF1670dtex / 2+PA1400dtex / 1) was treated with the first and second impregnation solutions prepared in Example 8. The impregnation treatment method was the same as in Example 8.

[0208] Comparative Example 1

[0209] Comparative Example 1 is a traditional RFL impregnation system.

[0210] Preparation of traditional RFL impregnation system: 0.1 parts by weight of sodium hydroxide and 100 parts by weight of deionized water were added to a beaker and stirred vigorously at 500 rpm for 10 min with an electric stirrer. Then, 3.7 parts by weight of resorcinol were added and stirred for 10 min. Finally, 5.4 parts by weight of formaldehyde aqueous solution (37 wt%) were added and stirred at room temperature for 6 h to obtain a homogeneous reaction solution. 80 parts by weight of styrene-butadiene-vinylpyridine latex (solid content 40 wt%) were added and stirred at room temperature for 20 h. Before the end of stirring, 1 part by weight of ammonia water was added to finally obtain the RFL impregnation solution.

[0211] RFL impregnation treatment method: The fiber cord is immersed in the impregnation solution for 3 seconds, and then dried and cured in an oven. The drying temperature is 150℃, the drying time is 72s, and the curing temperature is 225℃, the curing time is 72s; thus, impregnated cord is obtained. The fiber cord is Nylon 66 (1400 dtex / 2).

[0212] Comparative Example 2

[0213] Comparative Example 2 is a traditional RFL impregnation treatment.

[0214] First bath impregnation solution components:

[0215] 1.5 parts by weight of sorbitol glycidyl ether;

[0216] 3.7 parts by weight of ε-lactam-terminated diphenylmethane diisocyanate;

[0217] 100 parts by weight of deionized water.

[0218] Second bath impregnation solution components:

[0219] 100 parts by weight of deionized water;

[0220] 3.7 parts by weight of resorcinol;

[0221] Formaldehyde (37wt%) 5.4 parts by weight;

[0222] Sodium hydroxide (100wt%) 0.1 parts by weight;

[0223] 100 parts by weight of VP latex (40 wt% solids content);

[0224] 1.0 part by weight of ammonia water.

[0225] The VP latex is a styrene-butadiene-vinylpyridine latex.

[0226] Preparation method of the first bath impregnation solution: Sorbitol glycidyl ether, ε-caprolactam-terminated diphenylmethane diisocyanate and deionized water are added to a beaker in proportion and stirred vigorously at 500 rpm for 1 hour at 25°C to obtain the first bath impregnation solution.

[0227] Preparation method of the second bath impregnation solution: Sodium hydroxide and deionized water are added to a beaker and stirred vigorously at 500 rpm for 10 min with an electric stirrer. Then, resorcinol is added and stirred for another 10 min. Finally, formaldehyde aqueous solution (37 wt%) is added and stirred at room temperature for 6 h to obtain a homogeneous reaction solution. The reaction solution is added to VP latex (solid content 40 wt%) and stirred at room temperature for 1 h. Before the stirring is finished, ammonia water is added to finally obtain the second bath impregnation solution.

[0228] RFL impregnation treatment method: First, the fiber is placed in the first impregnation bath, impregnated for 3 seconds at room temperature, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds. Then, the fiber is placed in the second impregnation bath, impregnated for 3 seconds at room temperature, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds; thus obtaining the impregnated cord. The fiber cord is a high-denier nylon cord (2100 dtex / 3).

[0229] Comparative Example 3

[0230] The aramid cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Comparative Example 2. The impregnation treatment method was the same as in Comparative Example 2.

[0231] Comparative Example 4

[0232] The polyester cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Comparative Example 2.

[0233] RFL impregnation treatment method: First, place the polyester (1670 dtex / 2) cord in the first impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds. Then, place the fiber in the second impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds to obtain the impregnated cord.

[0234] Comparative Example 5

[0235] The aramid-nylon hybrid cord (AF1670dtex / 2+PA1400dtex / 1) was treated with the first and second impregnation solutions prepared in Comparative Example 2. The impregnation treatment method was the same as in Comparative Example 2.

[0236] Performance testing

[0237] The fiber cords impregnated in Examples 1-14 and Comparative Examples 1-5 were subjected to H-pull-out test, peel test, interfacial fatigue life test and cord strength test. The results are shown in Tables 1 and 2.

[0238] H-Pull-out force test specimen preparation method: According to standard GB / T2942-2009, the standard rubber (the standard rubber formula adopts GB / T9101-2017) is completely wrapped on the impregnated cord, and then it is placed on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 136℃, the vulcanization time is 50min, and the vulcanization pressure is 15MPa.

[0239] Peel strength test specimen preparation method: Refer to standard GB / T40725-2021, completely cover the impregnated cord with standard rubber to prepare peel test specimens, and finally place them on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 160℃, the vulcanization pressure is 2.354MPa, and the vulcanization time is 20min.

[0240] Fatigue life test specimen preparation method: Refer to standard GB / T31333, completely cover the impregnated cord with standard rubber, and then place it on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 136℃, the vulcanization pressure is 5MPa, and the vulcanization time is 50min.

[0241] Vulcanizing mold dimensions: mold cavity depth 2mm, length 250mm, width 170mm, each sample width 20mm, spacing between samples 6mm, 10mm reserved on each side of the mold, and the thickness of the cover plate and the mold base plate is not less than 10mm.

[0242] Preparation method of fiber cord tensile strength test specimen: Following standard GB32108-2015, the strength of the cord was tested by holding force after the cord was coated with adhesive. The test cord length was 250 mm, and the tensile speed was 300 mm / min.

[0243] The H-pull-out force of the fiber cord is tested according to GB / T2942-2009, the peel force is tested according to GB / T40725-2021, the fatigue life is tested according to GB / T39639-2020, and the tensile strength is tested according to GB / T32108-2015.

[0244] Table 1

[0245]

[0246] Examples 1-5 and Comparative Example 1 all used a single-bath method to treat the fiber cords, and the fiber cords used were all nylon 66 cords (1400 dtex / 2).

[0247] Table 1 shows that the fatigue life of Examples 1-5 increased by 6.5-65.8% compared to Comparative Example 1. The fatigue life of Examples 1-5 significantly exceeded that of Comparative Example 1, indicating that Examples 1-5 exhibited better fatigue resistance. The tensile strength of Examples 1-5 was comparable to that of Comparative Example 1. The impregnation system used in Examples 1-5 was the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention, while Comparative Example 1 used a traditional RFL impregnation system. This demonstrates that, compared to the traditional RFL impregnation system, the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention can further improve the fatigue resistance of fibers without significantly damaging their strength or affecting their use.

[0248] Compared to Example 2, Example 1 showed significantly improved H-pull-out force, peel force, and fatigue life; the tensile strength of Example 1 was comparable to that of Example 2. The bio-based benzoxazine resin used in Example 2 was prepared by reacting vanillin, L-lysine, and tannic acid, while the bio-based benzoxazine resin used in Example 2 was prepared by reacting salicylaldehyde, L-lysine, and catechin. This indicates that compared to the bio-based benzoxazine resin solution prepared by reacting vanillin, L-lysine, and tannic acid, the bio-based benzoxazine resin solution prepared by reacting salicylaldehyde, L-lysine, and catechin exhibits better H-pull-out force, higher peel force, longer fatigue life, and better adhesion.

[0249] The H-pull-out force and peel force of Example 1 (without filler) are slightly higher than those of Comparative Example 1 (RFL system). The H-pull-out force of Example 3 (with unmodified filler) is about 10% higher than that of Comparative Example 1 (RFL system), and the peel force is about 13% higher. The H-pull-out force of Example 4 (with modified filler) is about 17% higher than that of Comparative Example 1 (RFL system), and the peel force is about 12% higher. The H-pull-out force of Example 5 (with modified filler and optimized impregnation process) is about 14% higher than that of the RFL treatment, and the peel force is about 28% higher. Compared to Comparative Example 1, Examples 1, 3, 4, and 5 show an increase in H-pull-out force of 5.1-13.8%, an increase in peel force of 8.4-27.7%, and an increase in fatigue life of 18.5-65.8%. This demonstrates that the novel bio-based environmentally friendly impregnation system has an excellent effect on improving the interfacial adhesion between fibers and rubber.

[0250] As can be seen from Examples 3 and 4, the addition of fillers can further enhance the H-pull-out force and peel force, thereby further improving the adhesion between fibers and rubber. Simultaneously, the modification of the fillers is beneficial for improving their dispersion effect in the impregnation solution; the adhesive effect of the impregnation system reinforced with modified fillers is further improved compared to the system reinforced with unmodified fillers.

[0251] Table 2

[0252]

[0253] Examples 6-14 and Comparative Examples 2-5 all employed a two-bath method to treat the fiber cords. Specifically, the fiber cords treated in Examples 6-8 and Comparative Example 2 were high-denier nylon cords (2100 dtex / 3); the fiber cords treated in Examples 9-10 and Comparative Example 3 were aramid cords (1670 dtex / 2); the fiber cords treated in Examples 11-12 and Comparative Example 4 were polyester cords (1670 dtex / 2); and the fiber cords treated in Examples 13-14 and Comparative Example 5 were aramid / nylon 66 retwisted cords (A1670 dtex / 1 + N1400 dtex / 2).

[0254] Table 2 shows that compared to Comparative Example 2, the peel force of Examples 6-8 increased by 2-16.5%, and the fatigue life increased by 43.2-111.2%. Compared to Comparative Example 2, the H-pull-out force of Examples 7-8 increased by 4.5-18.7%. The peel force and fatigue life of Examples 6-8 far exceed those of Comparative Example 2, indicating that Examples 6-8 exhibit better peel resistance and fatigue resistance. The tensile strength of Examples 6-8 is comparable to that of Comparative Example 2. The impregnation system used in Examples 6-8 is the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention, while Comparative Example 2 uses a traditional RFL impregnation system. This demonstrates that compared to the traditional RFL impregnation system, the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention can further improve the peel resistance and fatigue resistance of fibers without significantly damaging the fiber strength or affecting its use.

[0255] Compared to Comparative Example 3, Examples 9-10 showed an increase in H-pull force of 9.4-21.5%, a increase in peel force of 2.8-26%, and an increase in fatigue life of 18.7-52.5%. The H-pull force, peel force, and fatigue life of Examples 9-10 significantly exceeded those of Comparative Example 3, indicating that Examples 9-10 exhibited superior H-pull force, peel resistance, and fatigue resistance. The tensile strength of Examples 9-10 was comparable to that of Comparative Example 3. The impregnation system used in Examples 9-10 was the novel fiber surface impregnation system based on bio-based benzoxazine resin provided by this invention, while Comparative Example 3 used a traditional RFL impregnation system. This demonstrates that, compared to the traditional RFL impregnation system, the novel fiber surface impregnation system based on bio-based benzoxazine resin provided by this invention can further improve the peel resistance and fatigue resistance of fibers without significantly damaging the fiber strength or affecting its use.

[0256] Compared to Comparative Example 4, Examples 11-12 showed an increase in H-pull force of 7-11.7%, a peel force of 21.9-38.6%, and a fatigue life of 140.7-170.1%. The H-pull force, peel force, and fatigue life of Examples 11-12 significantly exceeded those of Comparative Example 4, indicating that Examples 11-12 exhibited superior H-pull force, peel resistance, and fatigue resistance. The tensile strength of Examples 11-12 was comparable to that of Comparative Example 4. The impregnation system used in Examples 11-12 was the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention, while Comparative Example 4 used a traditional RFL impregnation system. This demonstrates that, compared to the traditional RFL impregnation system, the novel fiber surface impregnation treatment system based on bio-based benzoxazine resin provided by this invention can further improve the peel resistance and fatigue resistance of fibers without significantly damaging the fiber strength or affecting its use.

[0257] Compared to Comparative Example 5, Examples 13-14 showed an increase in H-pull force of 12.6-14.8%, a peel force of 13.9-23.6%, and a fatigue life of 31.2-71.8%. The H-pull force, peel force, and fatigue life of Examples 13-14 significantly exceeded those of Comparative Example 5, indicating that Examples 13-14 exhibited superior H-pull force, peel resistance, and fatigue resistance. The tensile strength of Examples 13-14 was comparable to that of Comparative Example 5. The impregnation system used in Examples 13-14 was the novel fiber surface impregnation system based on bio-based benzoxazine resin provided by this invention, while Comparative Example 5 used a traditional RFL impregnation system. This demonstrates that, compared to the traditional RFL impregnation system, the novel fiber surface impregnation system based on bio-based benzoxazine resin provided by this invention can further improve the peel resistance and fatigue resistance of fibers without significantly damaging the fiber strength or affecting its use.

[0258] This invention demonstrates that the novel fiber surface impregnation system based on bio-based benzoxazine resin provided by this invention exhibits excellent adhesion. The adhesion strength of various cords (high-denier nylon 66, aramid, polyester, and aramid-nylon blends) reaches or even exceeds the adhesion level of traditional RFL treatment, and its dynamic adhesion effect surpasses that of the traditional RFL system. Furthermore, comparisons of Examples 7-8, 9-10, 11-12, 13-14, and 16-17 show that the addition of modified filler further enhances the adhesion between the fiber and rubber, which is consistent with the results of the single-bath treatment of nylon 66 cords in Examples 2-4. In addition, the tensile strength of high-denier nylon 66 cords, aramid cords, polyester cords, and aramid-nylon blends did not change significantly after impregnation, indicating that this method does not damage the strength of the fiber itself and does not affect the fiber's performance.

Claims

1. A novel fiber surface treatment impregnation system, characterized in that, The impregnation system comprises the following components; Each component is expressed in parts by weight: 10-30 parts by weight of bio-based benzoxazine resin solution, preferably 15-25 parts by weight.

2. The impregnation system as described in claim 1, characterized in that, Solvent A is an aqueous solvent, preferably water, more preferably deionized water; or / and, The rubber latex is selected from one or more of the following: butyl rubber latex, styrene-butadiene rubber latex, styrene-butadiene rubber latex, chloroprene rubber latex, nitrile rubber latex, chlorosulfonated polyethylene latex, and natural latex; the styrene-butadiene rubber latex is preferably carboxyl-based styrene-butadiene rubber latex; the nitrile rubber latex is preferably carboxyl-based nitrile rubber latex; the natural latex is preferably epoxidized natural latex; or / and, The solid content of the rubber latex is 20-60 wt%; or / and, The filler is selected from one or more of the following: nano-silica, carbon black, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, nano-calcium oxide, nano-calcium carbonate, carbon nanotubes, attapulgite, nano-cellulose, malachite, nano-aramid fiber, basalt fiber, nano whiskers, graphene oxide, montmorillonite, mica, kaolin, and hydrotalcite, preferably one or more of the following: nano-cellulose, nano-silica, montmorillonite, and carbon nanotubes; or / and, The filler is a filler treated with a surface modifier; the surface modifier is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, alkylsilane coupling agents, isocyanate-based silane coupling agents and polyether silane coupling agents, preferably from one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, bis-[γ-(triethoxysilyl)propyl]tetrasulfide and vinyltriethoxysilane.

3. The impregnation system as described in claim 1, characterized in that, The bio-based benzoxazine resin solution contains the following repeating structural units:

4. The impregnation system as described in claim 1, characterized in that, The number-average molecular weight of the bio-based benzoxazine resin in the bio-based benzoxazine resin solution is 500-3000.

5. The impregnation system as described in claim 1, characterized in that, The bio-based benzoxazine resin solution contains 15-50 wt% bio-based benzoxazine resin, preferably 25-45 wt%.

6. The impregnation system as described in claim 1, characterized in that, The bio-based benzoxazine resin solution is prepared from raw materials comprising the following components; Each component is expressed in parts by weight: Solvent B, 20 parts by weight; 3-8 parts by weight of bio-based aldehyde, preferably 4-7 parts by weight; 1-5 parts by weight of bio-based polyamines, preferably 3-5 parts by weight; 0.1-5 parts by weight of bio-based polyphenols, preferably 3-5 parts by weight.

7. The impregnation system as described in claim 6, characterized in that, The solvent B is an aqueous solvent, preferably water, more preferably deionized water; or / and, The bio-based aldehyde is selected from one or more of salicylaldehyde, 5-hydroxymethylfurfural, vanillin, eugenol, cinnamaldehyde, benzaldehyde, phenylacetaldehyde, and cinnamaldehyde, preferably one or more of salicylaldehyde, 5-hydroxymethylfurfural, and vanillin; or / and, The bio-based polyamine is selected from one or more of L-lysine, furfurylamine, chitosan, and natural melanin, preferably one or more of L-lysine and furfurylamine; or / and, The bio-based polyphenols are selected from one or more of catechins, tea polyphenols, tannic acid, guaiacol, lignin, apigenin, resveratrol, naringenin, gallic acid, catechins, and apple polyphenols, preferably one or more of catechins, tea polyphenols, tannic acid, and lignin.

8. The impregnation system as described in claim 6, characterized in that, The preparation method of the bio-based benzoxazine resin solution includes: adding bio-based aldehyde to solvent B and stirring to dissolve it at 30-50℃, adding bio-based polyamine and stirring to react for 1-3 hours, and adding bio-based polyphenol and stirring to react for 3-8 hours.

9. A method for impregnating a fiber surface, characterized in that, The impregnation method includes: Step 1): Place the fiber in the impregnation system as described in any one of claims 1-8, and impregnate at 15-40°C for 2-60 seconds. Step 2): After impregnation, remove the fiber and dry it at 100-150℃ for 1-10 minutes, then cure it at 180-260℃ for 1-10 minutes.

10. The impregnation method as described in claim 9, characterized in that, Before step 1), the fibers are immersed in the impregnation solution at 15-40°C for 2-30 seconds, then removed and dried at 100-150°C for 1-10 minutes, and cured at 180-260°C for 1-10 minutes; preferably, by weight, the impregnation solution comprises: 100 parts by weight of solvent; 0.5-4 parts by weight of epoxy resin, preferably 0.5-2.5 parts by weight; 2-10 parts by weight of blocked isocyanate, preferably 4-8 parts by weight; or / and, Before step 1), the pH of the impregnation system is adjusted to alkaline using an alkaline solution, preferably between 8.0 and 11.0.

Citation Information

Patent Citations

  • Adhesive composition for adhering textiles to EPDM rubber

    US20050147817A1

  • Method for adhering fabric to rubber, treated fabric, and fabric-rubber composites

    US20050255773A1

  • Adhesive composition for organic fiber cords, rubber-reinforcing material using same, tire and bonding method

    US20120041113A1

  • Dipping material for cord fabrics and a production method thereof

    US20150259560A1

  • Tyre for vehicle wheels

    US20150314644A1